Suspect residual cyst at maxilla with sinus maxilaris involvement - Damayanti, Merry Annisa; Dhiaulhaq, Rifarana Inayah; Medika, Chrisna Ardhya; Jamil, Nur Aini; Munasyifa, Tazkia (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This case report aims to describe the radiographic characteristics of residual cysts in the maxilla that extend into the vestibular area and the maxillary sinus, using panoramic and CBCT radiographs. Case Report: An 81-year-old patient presented with a chief complaint of re-swelling after cyst removal under local anesthesia and scraping in 2022. The patient changed doctors and had a CBCT examination as a supporting examination to confirm the diagnosis. The patient had a history of hypertension and cholesterol, so treatment was delayed until now. Clinical examination showed vestibular swelling around the edentulous sites of teeth #13 and 14. Radiological examination showed a well-demarcated and well-defined radiolucency in the maxilla that was aggressive due to its relatively large size, erosion of the buccal cortical bone, and extension into the maxillary sinus. The suspected diagnosis of this case was a residual cyst due to previous treatment, with differential diagnoses of labial cyst, nasopalatine cyst, and radicular cyst. Conclusion: Based on clinical examination, radiography examination by 2D, panoramic, and 3D CBCT, this lesion is radiolucent, leading to a suspected radiodiagnosis of maxillary residual ar cyst with maxillary sinus involvement.